Rolled‐crimped cover crops for organic no‐till planted winter wheat (Triticum aestivum) in the Northeast region of the United States - Matthew R. Ryan; Terry J. Rose; Sandra Wayman; Christopher J. Pelzer; Uriel D. Menalled (Agrosystems, Geosciences & Environment)
Abstract Mulch from cover crops can suppress weeds and facilitate organic no‐till corn and soybean production. However, research is lacking on the no‐till planting small grain crops into rolled‐crimped cover crops. An experiment was conducted to test the effects of no‐till planting winter wheat (Triticum aestivum L.) into five cover crops planted in early summer, mid‐summer, and late summer. Cover crops were terminated with a roller‐crimper, and winter wheat was simultaneously no‐till planted in early fall. A “no cover crop” control treatment was also included, where wheat was planted into tilled soil. Cover crop and weed biomass at wheat planting varied by cover crop planting date and species. Early‐summer‐planted sorghum sudangrass [Sorghum bicolor (L.) Moench × S. sudanense (Piper) Stapf.] produced the most cover crop biomass and had among the lowest weed biomass at wheat planting and wheat harvest. However, wheat seedling density and grain yield were relatively low in the early‐planted sorghum sudangrass treatment compared with the other cover crop treatments, indicating a tradeoff between weed suppression and wheat yield. Early‐planted buckwheat (Fagopyrum esculentum Moench) and early‐planted soybean [Glycine max (L.) Merr.] had among the highest wheat grain yields, but no treatments yielded more than the “no cover crop” control. Wheat grain nitrogen was variable and may have been impacted by multiple factors, including wheat density. Results from this experiment indicate that rolled‐crimped cover crops can facilitate organic no‐till winter wheat production, but more research is needed to overcome tradeoffs and optimize production.